2010
DOI: 10.1074/jbc.m109.063057
|View full text |Cite
|
Sign up to set email alerts
|

TEAD-1 Overexpression in the Mouse Heart Promotes an Age-dependent Heart Dysfunction

Abstract: TEA domain transcription factor-1 (TEAD-1) is essential for proper heart development and is implicated in cardiac specific gene expression and the hypertrophic response of primary cardiomyocytes to hormonal and mechanical stimuli, and its activity increases in the pressure-overloaded hypertrophied rat heart. To investigate whether TEAD-1 is an in vivo modulator of cardiac specific gene expression and hypertrophy, we developed transgenic mice expressing hemagglutinin-tagged TEAD-1 under the control of the muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 96 publications
(98 reference statements)
4
41
0
Order By: Relevance
“…TEF family transcription factors are the major target of 1 adrenaline signaling (Chen et al, 2004), which is known to mimic the cardiac phenotype seen in heart failure (Yoshida, 2008). Consistently, overexpression of TEF-1 in vivo exhibits a phenotype similar to that of chronic heart failure (Tsika et al, 2010). Our preliminary data suggests that T3/TR inhibits TEF-dependent transactivation of the MHC gene.…”
Section: Possible Involvement Of the Tethering Mechanismsupporting
confidence: 49%
“…TEF family transcription factors are the major target of 1 adrenaline signaling (Chen et al, 2004), which is known to mimic the cardiac phenotype seen in heart failure (Yoshida, 2008). Consistently, overexpression of TEF-1 in vivo exhibits a phenotype similar to that of chronic heart failure (Tsika et al, 2010). Our preliminary data suggests that T3/TR inhibits TEF-dependent transactivation of the MHC gene.…”
Section: Possible Involvement Of the Tethering Mechanismsupporting
confidence: 49%
“…74 On the other hand, TEAD1 overexpression in the postnatal mouse heart upregulates the fetal-type gene program and induces age-dependent dysfunction. 75 These findings suggest that Yap-TEAD interaction is necessary for embryonic heart growth fully elucidated. However, it is known that the Hippo pathway plays a crucial role in regulating cardiac development.…”
Section: Hippo Pathway In Heart Developmentmentioning
confidence: 84%
“…While, a decrease in Serca2a and Pln phosphorylation was seen in these mice with heart failure, it is unclear if these were secondary to heart failure. Interestingly, both Tead1-overexpressing transgenic (42) and Tead1-deleted mice from our study displayed decreased contractile function. Consistent with the Tsika et al study that Tead1 overexpression upregulated β-MHC, Tead1-deletion, in our study, led to a significant decrease in β-MHC (data not shown), suggesting that Tead1 is a potent regulator of β-MHC.…”
Section: Discussionmentioning
confidence: 99%